Conflict of interest - Rosenberg, Nancy Taylor (New York : Hyperion, 2002)
District Attorney Joanne Kuhlman is struggling to put her own life together after the trauma of retrieving her children from her ex-husband who had kidnapped them. Now she must make a decision that could end her career. While trying three defendants for robbery, Joanne discovers a far more serious crime may be unfolding. One of the defendants is ignorant of the true nature of the crime. His attorney and mother insist he was cruelly exploited by his crime partners. When the young man disappears, Joanne fears he may have been murdered in a ruthless act to silence him. Her sympathies for this defendant lead her to entangle herself with his attractive attorney and compromise her career so the truth may be revealed.
National College of Business and Arts
Keywords: Public prosecutors -- Fiction; Fiction